Eye-tracking biomarkers for glaucoma based on saccadic reaction time: a controlled clinical study - Sverstad, Alexander; Helland-Hansen, Bjørn André; Kristianslund, Olav; Kolko, Miriam; Larsen, Stig Einride; Petrovski, Goran (Frontiers in Ophthalmology, 2025)
PurposeEvaluate the validity and reliability of saccadic reaction time (SRT)-based variables obtained using the novel eye-tracking device Bulbicam (BCAM) in differentiating early-to-moderate glaucoma (GLA) from healthy controls (HCs) and to identify potential biomarkers for GLA.MethodsA controlled clinical study was conducted, involving 18 GLA-patients, and 18 age-matched HCs. Participants underwent BCAM’s visual field (VF) test, which measures SRT at 58 symmetrically arranged locations with 6° spacing. Variables were analysed for group differences, within- and between-patient repeatability, and stability. To evaluate their potential as biomarkers, VF locations were aggregated into clusters, quadrants, hemifields, and whole VF analyses.ResultsSignificant SRT differences (p ≤ 0.05) were observed between GLA and HC in 44 of 58 locations in the worst eye and 42 of 58 in the best eye. Eight out of ten clusters met the criteria for BCAM biomarkers having significant group differences, sufficient within- and between-patient repeatability, and adequate stability. All quadrants demonstrated excellent stability and repeatability thereby qualifying as biomarkers. Hemifield SRTs were reliable, however, the absolute difference between hemifields showed poor within-participant repeatability. The mean and standard deviation of SRT for the whole VF were identified as significant biomarkers with excellent stability.ConclusionsThe majority of SRT variables are capable of differentiate glaucomatous eyes from HC while maintaining sufficient reliability and stability for clinical application. 19 of 22 BCAM VF test variables were found to be potential GLA-biomarkers.Clinical Trial Registrationhttps://clinicaltrials.gov/, identifier NCT05449041.